Repetition of biochemistry tests in a laboratory of public hospital in southwest of Bahia, Brazil, and associated cost - Márlon S. P. Rodrigues; Claudio L. Souza; Márcio V. Oliveira (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: Test repetitions are an age-old practice common to clinical laboratories used primarily for confirmation of results. However, knowing the history of patients, the repetitions become avoidable. They impair the time to release results, increase input consumption, and cost of services. Objectives: to evaluate the difference between the results of the laboratory tests repetitions and the expenditure generated by each additional test. Materials and methods: Data from repeated tests from September to November 2015 were used in the laboratory of a public hospital in the state of Bahia, Brazil. The classification of necessary or unnecessary repetition of these tests was performed according to international criteria, with subsequent cost estimation. Results: A total of 1,350 samples were analyzed, with a total of 1,429 repetitions; 1,162 (81.31%) were classified as unnecessary repetitions, generating an additional cost of R$ 1,198.00 to the service. The repetitions that made up the study generated a cost of R$ 1,488.61, the expense should be only R$ 290.61, an increase of 80.47%, an estimated annual impact of R$ 4,792.00. In addition to the impact on cost, the impact on turnaround time was evident, which consequently affects the speed in patient care. Conclusion: It was observed that most of the repetitions performed in the laboratory were classified as unnecessary when evaluated by the criteria used. These repetitions generated a potentially avoidable laboratory cost increase, negatively impacting the time to release the results.